What general emergency nurses want to know about mental health patients presenting to their emergency department - Kerrison, Shirilee; Chapman, Rose (Elsevier, 2007)
This paper presents the findings of a qualitative project conducted to investigate the education and training requirements that non - mental health trained emergency nurses need to enable them to effectively care for psychiatric patients presenting to a West Australian emergency department. Non-mental health trained nurses are ill-equipped in their psychiatric knowledge, assessment and communication skills to provide best possible care to the one in ten patients presenting to the emergency department with a complex mental health issue. The area of assessment and management of mental health patients in the emergency department is a complex one and staff are required to assess, triage and manage these patients appropriately. Furthermore, with aggression and violence increasing, emergency department nurses are concerned about their safety in the workplace. Focus groups with emergency nurses and semi-structured interviews with subject matter experts were conducted at one West Australian teaching hospital. The findings of the project demonstrated that these nurses considered that customer focus, workplace aggression and violence, psychiatric theory, mental health assessment and chemical dependence as key learning areas. These findings will form a platform for further education and training for ED staff.